A roadmap for next-generation nanomotors - Chen, Shuqin; Fan, Donglei Emma; Fischer, Peer; Ghosh, Ambarish; Göpfrich, Kerstin; Golestanian, Ramin; Hess, Henry; Ma, Xing; Nelson, Bradley J.; Patiño Padial, Tania; Tang, Jinyao; Villa, Katherine; et al. (Nature nanotechnology, 2025)
Since their discovery in 2004, there has been remarkable progress in research on nanomotors, from the elucidation of different propulsion mechanisms to the study of their collective behaviour, culminating in investigations into their applications in biomedicine and environmental remediation. This Perspective reviews this evolution in nanomotor research and discusses the key challenges ahead, including the need for developing advanced characterization techniques, precise motion control, materials innovation, theory and modelling, and translationally feasible in vivo biomedical applications. These challenges highlight the current limitations of synthetic nanomotors and point to exciting future opportunities to revolutionize theranostics and create ‘living’ hybrid systems. We introduce the concept of ‘systems materials’ to encompass interacting functional materials across length scales from molecular to macro. Thus, this Perspective aims to inspire future generations of researchers to advance both fundamental understanding and practical breakthroughs, thereby engineering a paradigm shift in nanomotor research.